ANALISIS PENGENDALIAN INTERNAL, KESADARAN ANTI-FRAUD, DAN PENGETAHUAN FRAUD TERHADAP PENCEGAHAN FRAUD - Debora Kartini Miseri Lubis; Gideon Setyo Budiwitjaksono (Jambura Economic Education Journal, 2023)
Analyzing and empirically testing the influence of internal control, anti-fraud awareness, and fraud knowledge on fraud prevention is the purpose of this study. Internal control variables, anti-fraud awareness, and fraud knowledge are independent variables and fraud prevention are the dependent variables of this study. The study used quantitative methods with primary data as a data source through the dissemination of questionnaires. All organic employees of 35 employees in the Branch Office of Bank Rakyat Indonesia (BRI) Surabaya Pahlawan are the population used in this study. The use of saturated sampling techniques by designating the entire population as a sample is a sampling technique used in this study. Multiple linear analysis is an analysis technique used that is processed with the help of SPSS version 22. The results revealed that internal control has no influence on fraud prevention. However, anti-fraud awareness and fraud knowledge have a positive influence on fraud prevention.